The Possibilities of the Microcontroller based implementation of the Generic Bi-layered Net Model - Bánkuti, Gyöngyi; Bálint, János (Acta Agraria Kaposváriensis, 2006)
In our paper we deal with the PIC based hardware implementation of the Generic Bilayered Net Model, patented by the Process-informatics Research Group of the University of Kaposvár. As their is no adequate hardware to implement this well-tried software methodology, our aim was only to construct the structure of a simple small problem, and to examine it. We present the microcontroller based implementation of the structure and it’s programming, from the initialing, testing, to the four step execution, the circuit schematics and the photos of the integrated circuits as well.